Elevated adipokines and myokines are associated with fatigue in long COVID patients - Nina R. G. Visconti; Nazareth N. Rocha; Nazareth N. Rocha; Gabriela S. Nascimento; Caio V. B. Menário; Johnatas D. Silva; Camila M. Martins; Celso Caruso-Neves; Fernanda F. Cruz; Patricia R. M. Rocco; Fernanda C. Q. Mello; José R. Lapa-e-Silva (Frontiers in Medicine)
BackgroundPersistent fatigue is one of the most common and debilitating symptoms experienced by patients recovering from COVID-19, contributing significantly to the burden of “long COVID” or post-COVID-19syndrome. However, the underlying pathophysiological mechanisms remain inadequately understood. Few studies have examined the association between fatigue and pulmonary or cardiac function, systemic biomarkers, or morphological changes in the lungs and diaphragm. Furthermore, the potential influence of vaccination on the persistence of fatigue has not been fully explored. This study aims to identify mechanisms contributing to post-COVID-19 fatigue.MethodsThis prospective cohort study assessed clinical, laboratory, pulmonary, and cardiac parameters, as well as diaphragm ultrasound and pulmonary function, in patients with and without fatigue at least 4 months after discharge from hospitalization due to COVID-19.ResultsOf 88 patients evaluated, 34% reported new or worsening fatigue after recovering from COVID-19. Demographic characteristics, comorbidities, and vaccination status were similar between fatigued and non-fatigued groups. However, ICU admission during the acute phase of illness emerged as a significant risk factor for fatigue (OR 2.65; 95% CI, 1.03–6.94) in multivariable analysis. No significant differences were observed in lung function, diaphragm or lung ultrasound findings, or left ventricular systolic function between groups. Fatigue was associated with significantly elevated serum levels of myostatin and irisin, markers of muscle metabolism. Additionally, patients experiencing fatigue reported poorer functional capacity and significantly reduced quality of life, with lower scores in multiple domains of the SF-36 questionnaire, including general health, vitality, and mental health.ConclusionPost-COVID-19 fatigue is strongly associated with prior ICU admission and elevated levels of myostatin and irisin, implicating potential myopathic mechanisms in its persistence. The profound impact of fatigue on functional capacity and quality of life highlights the urgent need for further research to elucidate its pathophysiology and develop targeted therapeutic strategies. This study provides critical insights into the interplay between systemic and organ-specific factors contributing to fatigue, offering a foundation for future interventions to improve outcomes in patients with long COVID.